2017
DOI: 10.1038/s41598-017-06963-w
|View full text |Cite
|
Sign up to set email alerts
|

Scheduled feeding restores memory and modulates c-Fos expression in the suprachiasmatic nucleus and septohippocampal complex

Abstract: Disruptions in circadian timing impair spatial memory in humans and rodents. Circadian-arrhythmic Siberian hamsters (Phodopus sungorus) exhibit substantial deficits in spatial working memory as assessed by a spontaneous alternation (SA) task. The present study found that daily scheduled feeding rescued spatial memory deficits in these arrhythmic animals. Improvements in memory persisted for at least 3 weeks after the arrhythmic hamsters were switched back to ad libitum feeding. During ad libitum feeding, locom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…However, anticipatory activity does not appear in the absence of a circadian injection schedule ( Iijima et al, 2002 ), indicating that entrainment of the circadian timing system is required for the anticipation to develop. More evidence of a circadian component to anticipation is available in changes in c-FOS expression in anticipation of a daily meal, with studies in rats ( Challet et al, 1997 ; Angeles-Castellanos et al, 2004, 2007 ; Mendoza et al, 2005 ; Escobar et al, 2007 ; Poulin and Timofeeva, 2008 ; Acosta-Galvan et al, 2011 ; Mitra et al, 2011 ; Caba et al, 2014 ), mice ( Begriche et al, 2012 ; Blum et al, 2012 ; Gallardo et al, 2014 ; Dattolo et al, 2016 ; Luna-Illades et al, 2017 ), and hamsters ( Dantas-Ferreira et al, 2015 ; Ruby et al, 2017 ), or in anticipation of a palatable treat in rats or mice ( Mendoza et al, 2005 ; Mitra et al, 2011 ; Gallardo et al, 2012 ; Blancas et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, anticipatory activity does not appear in the absence of a circadian injection schedule ( Iijima et al, 2002 ), indicating that entrainment of the circadian timing system is required for the anticipation to develop. More evidence of a circadian component to anticipation is available in changes in c-FOS expression in anticipation of a daily meal, with studies in rats ( Challet et al, 1997 ; Angeles-Castellanos et al, 2004, 2007 ; Mendoza et al, 2005 ; Escobar et al, 2007 ; Poulin and Timofeeva, 2008 ; Acosta-Galvan et al, 2011 ; Mitra et al, 2011 ; Caba et al, 2014 ), mice ( Begriche et al, 2012 ; Blum et al, 2012 ; Gallardo et al, 2014 ; Dattolo et al, 2016 ; Luna-Illades et al, 2017 ), and hamsters ( Dantas-Ferreira et al, 2015 ; Ruby et al, 2017 ), or in anticipation of a palatable treat in rats or mice ( Mendoza et al, 2005 ; Mitra et al, 2011 ; Gallardo et al, 2012 ; Blancas et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, recently, it has been reported that mistimed feeding results in changes of clock molecules in the hippocampus (corticolimbic) while SCN remains unchanged. This misalignment results in hippocampal-dependent learning impairment ( 26 ). The most provocative finding is that despite the positive effect of NIF on learning, CR is still a more efficient intervention on learning and memory, while inappropriate food intake time inversely affects learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Other forms of regulation, such as posttranslational modifications, found in the case of the casein kinase CK1δ, further modulate cellular activity as a function of circadian period (25,34). The clock is tightly integrated with metabolism (35), and together these processes influence much of human biology, including hormone balance (36), feeding habits (37) and digestion (38), body temperature, cognition, and many more (35,39). The Journal of Clinical Investigation 69).…”
Section: Extremes Of Chronotype and Geneticsmentioning
confidence: 99%